Peran religionsity sebagai pemoderasi hubungan money ethics terhadap upaya tax evasion - Oktaviani, Rachmawati Meita; Srimindarti, Ceacilia; Hardiningsih, Pancawati (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2018)
The purpose of this study was to examine and analyze the influence of money ethic, intrinsic and extrinsic religionsity against tax evasion. In addition to test and analyze the effects of intrinsic and extrinsic religionsity as moderating the relationship between money ethics against tax evasion. The theory rooted in selfishness that tax evasion action is not considered a violation because the act of self is not an ethics violation. While different views in the Theory of Ethics Teonom that, tax evasion is an act of abuse of religion because religion is recommended to give us what we have to help others poeple. Metode study is a quantitative method by distributing questionnaires to 113 individual taxpayers at the Tax Office in Semarang. The sampling technique used is convenience sampling. While data analysis technique used in this research is regression test moderation absolute difference using SPSS. The results showed that money ethics and intrinsic religionsity influence on tax evasion, while the extrinsic religionsity no effect on tax evasion. While variable intrinsic religionsity in this study proved to be moderate the relationship money ethics against tax evasion. But diferrent result showed extrinsic religionsty not moderate the relationship money ethics against tax evasion